William Marshal : Knight-Errant, Baron, and Regent of England - Painter, Sidney, 1902-1960 (Book collections on Project MUSE., 2019)
The rise to prominence of administrative law in the second half of the twentieth century is often remarked upon as the greatest legal development of the period. In this process there has been considerable borrowing of ideas and learning from experiences elsewhere in the common law world. This volume brings together administrative law scholars and judges from around the globe to address important issues in the field and to honour the career of one of the leading administrative lawyers in the Anglo-Commonwealth world, Professor David Mullan. Editors Grant Huscroft and Michael Taggart have identified the broad themes in Mullan's work - procedural fairness; scope of review and deference; the interrelationship of administrative law and human rights; the legitimacy of state regulation and tribunal adjudication; common law comparativism - and invited contributions on those themes from leading scholars in Canada, the United Kingdom, Australia, South Africa, and the United States. A fitting tribute to a great scholar, Inside and Outside Canadian Administrative Law will prove fascinating to students, teachers, and practitioners of administrative law as well as policy makers and political scientists.